Temperate performance and metabolic adaptations following endurance training performed under environmental heat stress - Maunder, E.; Plews, D. J.; Wallis, G. A.; Brick, M. J.; Leigh, W. B.; Chang, W.-L.; Watkins, C. M.; Kilding, A. E. (Physiological Reports, 2021)
Endurance athletes are frequently exposed to environmental heat stress during training. We investigated whether exposure to 33°C during training would improve endurance performance in temperate conditions and stimulate mitochondrial adaptations. Seventeen endurance-trained males were randomly assigned to perform a 3-week training intervention in 18°C (TEMP) or 33°C (HEAT). An incremental test and 30-min time-trial preceded by 2-h low-intensity cycling were performed in 18°C pre- and post-intervention, along with a resting vastus lateralis microbiopsy. Training was matched for relative cardiovascular demand using heart rates measured at the first and second ventilatory thresholds, along with a weekly "best-effort" interval session. Perceived training load was similar between-groups, despite lower power outputs during training in HEAT versus TEMP (p < .05). Time-trial performance improved to a greater extent in HEAT than TEMP (30 ± 13 vs. 16 ± 5 W, N = 7 vs. N = 6, p = .04), and citrate synthase activity increased in HEAT (fold-change, 1.25 ± 0.25, p = .03, N = 9) but not TEMP (1.10 ± 0.22, p = .22, N = 7). Training-induced changes in time-trial performance and citrate synthase activity were related (r = .51, p = .04). A group × time interaction for peak fat oxidation was observed (Delta 0.05 ± 0.14 vs. -0.09 ± 0.12 g·min-1 in TEMP and HEAT, N = 9 vs. N = 8, p = .05). Our data suggest exposure to moderate environmental heat stress during endurance training may be useful for inducing adaptations relevant to performance in temperate conditions. New findings